When You Choose but Not Lose: Decreasing People’s Desire for Options on Technological Appliances - Lemmen, Nieke; Bouman, Thijs; Steg, Linda (Frontiers in Psychology, 2022)
The appliances people adopt, and the way they use them, can critically influence the sustainable energy transition. People are often attracted to appliances with many setting options that offer them more control. Yet, operating many setting options can have negative consequences for users (e.g., user frustration) and the management of sustainable energy systems (e.g., unpredictable consumption increasing complexity and uncertainty of systems), which may obstruct sustainability goals. We aim to study how to reduce the preference for many setting options without reducing the perceived attractiveness of the appliance. In line with our theorizing we found that people opt for appliances with fewer setting options when they are asked to reflect on which options they would like to have from a list of possible setting options, while being equally satisfied with the appliance. In addition, we show that this is especially the case when asking people to select which setting options they would like an appliance to have, as this will feel like they gain options, rather than asking them which options they are willing to give up as this feels like losing options that their appliance could have. Our findings offer relatively easy and cost-efficient ways to decrease people’s desire for many setting options on appliances, decreasing stress on the user and the energy system, while ensuring satisfaction with and acceptance of the appliance.